Rapid Response Training (Q R T) in developing some physical abilities and skill performance among junior football players - Obed , Nahlah; Jasim , Shahad (Journal of Physical Education, 2024)
It requires different situations of responses such as speed in attack or speed in defense and for all members of the team, speed in decision-making and control of the ball and create better opportunities for a state of superiority and victory over the opposing team shows the importance of research in providing rapid response training (Q R T) in order to contribute to enhancing some physical abilities such as strength, speed, agility, handling and scoring skills. As for the problem of searching for a moment, some players cannot make a decision quickly, so they look at the goal and take time to make the decision and respond, which may cause the failure of the attack and lose possession due to the loss of the element of surprise and confusion of defenders. The research aimed to identify the impact of rapid response training (Q R T) in some physical abilities and skill performance of junior football players on specialized school players aged (14-16) years and the use of rapid response training exercises (Q R T) on the experimental group and concluded that the adoption of rapid response training (Q R T) works to develop some of the physical abilities of junior football players and recommended the need to design training programs to develop the speed of motor response ...